Respuesta :
Answer:
3
Step-by-step explanation:
12 times 3 = 36
36 times 6 = 216
12(x times 6)
(12)6x
72x
216 = 72x
216/72 = 3
Answer:
The number 3 makes this statement true.
[tex]x=3[/tex]
Step-by-step explanation:
Given the equation:
[tex](12*3)*6=12*(x*6)[/tex]
Using the order of operations, we can evaluate the terms in the parentheses through the process of multiplication:
[tex]36*6=12*6x[/tex]
Multiply the terms on both sides of the equation:
[tex]216=72x[/tex]
Finally, divide both sides of the equation by the coefficient of [tex]x[/tex], which is [tex]72[/tex]:
[tex]3=x[/tex]
[tex]x=3[/tex]
-
Let's check our work by substituting the solved [tex]x[/tex] value for
[tex](12*3)*6=12*(3*6)[/tex]
[tex]36*6=12*18[/tex]
[tex]216=216[/tex]
Since both sides of the equation are equal to each other, our solution is correct!